The genomes of precision edited cloned calves show no evidence for off-target events or increased de novo mutagenesis - Jivanji S; Harland C; Cole S; Brophy B; Garrick D; Snell R; Littlejohn M; Laible G (BioMed Central Ltd, 2021)
BACKGROUND: Animal health and welfare are at the forefront of public concern and the agricultural sector is responding by prioritising the selection of welfare-relevant traits in their breeding schemes. In some cases, welfare-enhancing traits such as horn-status (i.e., polled) or diluted coat colour, which could enhance heat tolerance, may not segregate in breeds of primary interest, highlighting gene-editing tools such as the CRISPR-Cas9 technology as an approach to rapidly introduce variation into these populations. A major limitation preventing the acceptance of CRISPR-Cas9 mediated gene-editing, however, is the potential for off-target mutagenesis, which has raised concerns about the safety and ultimate applicability of this technology. Here, we present a clone-based study design that has allowed a detailed investigation of off-target and de novo mutagenesis in a cattle line bearing edits in the PMEL gene for diluted coat-colour. RESULTS: No off-target events were detected from high depth whole genome sequencing performed in precursor cell-lines and resultant calves cloned from those edited and non-edited cell lines. Long molecule sequencing at the edited site and plasmid-specific PCRs did not reveal structural variations and/or plasmid integration events in edited samples. Furthermore, an in-depth analysis of de novo mutations across the edited and non-edited cloned calves revealed that the mutation frequency and spectra were unaffected by editing status. Cells in culture, however, appeared to have a distinct mutation signature where de novo mutations were predominantly C > A mutations, and in cloned calves they were predominantly T > G mutations, deviating from the expected excess of C > T mutations. CONCLUSIONS: We found no detectable CRISPR-Cas9 associated off-target mutations in the gene-edited cells or calves derived from the gene-edited cell line. Comparison of de novo mutation in two gene-edited calves and three non-edited control calves did not reveal a higher mutation load in any one group, gene-edited or control, beyond those anticipated from spontaneous mutagenesis. Cell culture and somatic cell nuclear transfer cloning processes contributed the major source of contrast in mutational profile between samples.
Keywords: Animals; CRISPR-Cas Systems; Cattle; Clustered Regularly Interspaced Short Palindromic Repeats; Gene Editing; Genome; Mutagenesis; Mutation